Direct Detection of Static Dipolar Interaction on a Single Nanodisk Using Microfocused Brillouin Light Scattering Spectroscopy. (30th March 2015) - Shimon, Goei; Adeyeye, Adekunle O.
<x xml:space="preserve">Abstract</x> Direct probing of how the static dipolar field from neighboring disk affects the dynamic behavior of a single disk using microfocused Brillouin light scattering spectroscopy is presented. Using pairs of identical Ni80Fe20 disks (diameter d = 500 nm) and by varying the inter‐disk spacing (s) in the range from 50 to 500 nm, a marked spectral and spatial shift in the resonant mode with increasing dipolar interaction (by reducing s) is demonstrated. When the disks are in a single domain state (at high magnetic field), the dipolar interaction is highly anisotropic depending on the relative orientation between the inter‐disk coupling direction and the applied field. The effect of dipolar interaction on the resonant frequency greatly diminishes when the disks are in a vortex state (at low field). Micromagnetic simulations and analytical calculations are in good agreement with our experimental results. The results and methodology presented in this work are useful in further development of high density magnetic recording media, functional microwave signal processing, and logic devices.